Enteric neuronal plasticity and a reduced number of interstitial cells of Cajal in hypertrophic rat ileum. Issue 6 (1st June 1998) - Ekblad, E; Sjuve, R; Arner, A; Sundler, F
Abstract : Background —Partial obstruction of the ileum causes a notable hypertrophy of smooth muscle cells and enteric neurones in the proximally located intestine. Aims —To study the expression of neuromessengers in the hypertrophic ileum of rat as little is known about neuromessenger plasticity under these conditions. To investigate the presence of interstitial cells of Cajal (ICC) in hypertrophic ileum. Methods —Ileal hypertrophy was induced by circumferential application of a strip of plastic film for 18–24 days. Immunocytochemistry, in situ hybridisation, nicotinamide adenine dinucleotide phosphate (NADPH) diaphorase histochemistry, and ethidium bromide staining were used to investigate the number of enteric neurones expressing neuropeptides and nitric oxide synthase, and the frequency of ICC. Results —In the hypertrophic ileum several neuronal populations showed changes in their expression of neuromessengers. Myenteric neurones expressing vasoactive intestinal peptide (VIP), pituitary adenylate cyclase activating peptide, and galanin were notably increased in number. In submucous ganglia the number of VIP immunoreactive neurones decreased while those expressing VIP mRNA increased. NADPH diaphorase positive submucous neurones increased dramatically while the number of neuronal type nitric oxide synthase expressing ones was unchanged. The number of ICC decreased notably in hypertrophic ileum. Conclusion —Enteric neurones change their levels of expression of neuromessengers in hypertrophic ileum. ICC are also affected. The changes are presumably part of an adaptive response to the increased work load.